THE ROLE OF EFFLUX PUMP FOR ANTIBIOTIC RESISTANCE IN BACTERIA: THE ROLE OF EFFLUX PUMP FOR ANTIBIOTIC RESISTANCE IN BACTERIA (Iraqi Journal of Market Research and Consumer Protection, 2022)
ABSTRACT                The multi-drug resistant efflux pump is a glycoprotein pump whose function is to push foreign substances. The efflux pump is found in humans, animals. It also has wide-ranging properties in  bacteria and fungi. They are found in all species of bacteria, and efflux pump genes can be found in bacterial chromosomes or mobile genetic elements, such as plasmids. The most sensitive function that leads to a global problem is its resistance to antibiotics in bacterial cells, which increases the ability to bacteria from becoming strong virulence factors that most or all antibiotics cannot kill. It also has other important functions. It is related to the defense mechanism of the horse by pushing all harmful substances. This pump is divided into five families. The division depends on the source of energy, symmetry, and the general structure. The major facilitator (MFS) superfamily; the multidrug and toxic compound extrusion (MATE) family and the adenosine-triphosphate (ATP)-binding cassette (ABC); superfamily the resistance-nodulation-cell division (RND) superfamily  and the small multidrug resistance (SMR). The ABC family uses ATP as a source of energy for export, while other flow pumps use the driving force of the proton. These hosts participate in many cellular processes such as intercellular communication, formation of cell membranes, virulence factors of bacterial cell, extrusion of toxic substances, disinfectants, toxic metabolic by-products, and antibiotics. It is also one of the important formations in bacteria that give bacteria the ability to expel antibiotics through various and diverse genes that are located either on the chromosome or plasmid of different pump families. Evidence indicates that the efflux pump has physiological functions in bacteria, and its overexpression has a role in inducing multi-drug resistance and biofilm formation. Hence, the regulation of efflux pump action is an orderly, strict action in response to physiological and environmental signals.